Cinematic Representations of Alzheimer's Disease - Medina, Raquel (Palgrave Macmillan UK, 2018)
This book offers a cross-cultural approach to cinematic representations of Alzheimer's disease in non-mainstream cinema. Even though Alzheimer's disease, the most common form of dementia, is a global health issue, it is not perceived or represented homogenously around the world. Contrary to very well-known mainstream films, the films discussed do not focus on the negative aspects normally associated with Alzheimer's disease, but on the importance of portraying the perspective of the persons living with Alzheimer's and their personhood. Similarly, this book analyses how the films use Alzheimer's as a trope to address issues relating to different areas of life and society such as, for example, family matters, intergenerational relationships, gender issues, national traditions versus global modernity, and caring for people with dementia. By examining an array of films, from crime fiction to documentary, that each present non-stigmatising representations of Alzheimer's disease, this in-depth study ultimately demonstrates the power of culture in shaping meaning.